Simultaneous Contralateral Breast Adjustment in Unilateral Deep Inferior Epigastric Perforator Breast Reconstruction - Inbal, Amir; Gur, Eyal; Otremski, Eran; Zaretski, Arik; Amir, Aharon; Weiss, Jerry; Barnea, Yoav (Journal of Reconstructive Microsurgery, 2012)
Background Breast symmetry is a key factor in deep inferior epigastric perforator (DIEP) flap breast reconstruction, which necessitates in many cases contralateral breast adjustment, traditionally done at a second stage. We present our experience with simultaneous contralateral breast adjustment in unilateral DIEP breast reconstruction.Methods We retrospectively reviewed all consecutive unilateral DIEP breast reconstructions done in our institution. The patients were divided into three groups according to contralateral breast surgery performed: simultaneous adjustment, late adjustment, and no contralateral breast adjustment surgery. The groups were compared by aesthetic outcome and patient satisfaction using the BREAST-Q questionnaire.Results A total of 77 unilateral breast reconstructions were performed using the DIEP flap. Fifty-one eligible patients agreed to respond to the questionnaire by telephone and were enrolled in the study; 33 underwent simultaneous contralateral breast adjustment, eight underwent late adjustment procedure, and 10 had no contralateral surgery performed. Aesthetic outcome and patient satisfaction was comparable in the simultaneous and late adjustment groups, but was reduced during the latent period.Conclusion Simultaneous contralateral breast adjustment in unilateral DIEP breast reconstruction is a safe and a worthwhile procedure that should be offered to the patient when appropriate.
Keywords: breast reconstruction; deep inferior epigastric perforator (DIEP); breast cancer; breast asymmetry; BREAST-Q